Research on Time-Dependent Component Importance Measures Considering State Duration and Common Cause Failure - Xu, Anqi; Zhang, Zhijian; Zhang, Huazhi; Wang, He; Zhang, Min; Chen, Sijuan; Ma, Yingfei; Dong, Xiaomeng (Frontiers in Energy Research, 2020)
Unlike the current Risk Monitors, Real-Time Online Risk Monitoring and Management Technology (RORMT) is characterized by time-dependent modeling on the state duration of components. Given the real-time plant configuration, it eventually provides the time-dependent risk level and importance measures for operation and maintenance management. This paper focuses on the assessment method of time-dependent importance measure and its risk-informed applications in RORMT, including Fussell-Vesely (FV), Risk Achievement Worth (RAW), Risk Reduction Worth (RRW). In this study, the values of component importance has been investigated with time-dependent risk quantification model, as well as the common cause failure (CCF) treatment model. Here three options of CCF treatment has been developed, assuming that unavailability of component could be due to an independent factor (Option 1), common cause factor (Option 2), or unconfirmed cause (Option 3). In the special case ‘what if a component is out-of-service’ of RAW numerator, a hybrid method for RAW evaluation is presented resulting in a balanced and reasonable RAW value. A simple case study was demonstrated. The results showed that the absolute values and ranking order of time-dependent importance not only reflected the effect of cumulative state duration of component on risk, but also comprehensively accounted for all possible situations of component unavailability. Moreover, time-dependent importance measures improve and provide novel insights for online configuration management, a) ranking SSCs/events/human actions for controlling increased risk and optimizing near–term plans; b) exempting or limiting temporary configurations during online operation.